Middleware untuk Otomatisasi dan Sinkronisasi Digital Signage pada Aplikasi Xibo - Dade, Claradisha Helenora; Kristanto, Bagus Kristomoyo (LPPM STIKI MALANG, 2023)
The Xibo digital signage application is a platform used to manage and display multimedia content on digital screens. However, the complexity of the workflow in using Xibo is often an obstacle. In order to overcome this challenge, this research provides a solution, namely, Xibo Middleware, a website-based intermediary application developed using PHP and the CodeIgniter 3 framework. Xibo Middleware aims to overcome the problem of workflow complexity in using Xibo. Its function is as a bridge between users and Xibo API, with a simpler interface. This application is designed to simplify content management and scheduling of multimedia content to display in digital signage applications. The main focus of this research is on the simplification and quality of using Xibo in digital signage content management.